2002
DOI: 10.1103/physrevlett.88.082501
|View full text |Cite
|
Sign up to set email alerts
|

Hypernuclear Fine Structure inBΛ9e

Abstract: With a germanium detector array (Hyperball), we observed two gamma-ray peaks corresponding to the two transitions (5/2(+)-->1/2(+) and 3/2(+)-->1/2(+)) in the (9)(Lambda)Be hypernucleus which was produced by the 9Be(K-,pi(-)) reaction. The energies of the gamma rays are 3029 +/- 2 +/- 1 keV and 3060 +/- 2 +/- 1 keV. The energy difference was measured to be 31.4(+2.5)(-3.6) keV, which indicates a very small Lambda-spin-dependent spin-orbit force between a Lambda and a nucleon. This is the smallest level splitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(50 citation statements)
references
References 23 publications
2
47
1
Order By: Relevance
“…1(c), this difference leads to the opposite level ordering of the the 0 doublets between the ND and NSC97f results, while these doublets are almost degenerated in the ESC08c result. It is found that the contribution from the spin-orbit interaction of ESC08c is less than 100 keV for 0 ± 1 and 1 ± 1 doublets, which is consistent with the observations in 9 Be [45,46] and 13 C [47,48]. Therefore, we consider that the uncertainty of the spin-orbit interaction has minor influence to the parity reversion compared to other uncertainties discussed above.…”
Section: Resultssupporting
confidence: 78%
“…1(c), this difference leads to the opposite level ordering of the the 0 doublets between the ND and NSC97f results, while these doublets are almost degenerated in the ESC08c result. It is found that the contribution from the spin-orbit interaction of ESC08c is less than 100 keV for 0 ± 1 and 1 ± 1 doublets, which is consistent with the observations in 9 Be [45,46] and 13 C [47,48]. Therefore, we consider that the uncertainty of the spin-orbit interaction has minor influence to the parity reversion compared to other uncertainties discussed above.…”
Section: Resultssupporting
confidence: 78%
“…Unlike the case of the N N interactions, hyperon interactions are not well determined experimentally due to insufficient number of scattering data. Nevertheless, high-resolution γ-ray experiments [2][3][4][5] analyzed by the shell model [6] as well as the accurate few-body method [7] have provided valuable constraints on the Y N interaction in the Strangeness = −1 sector such as the ΛN force. Also, the ΛΛ interaction in the Strangeness = −2 sector receives some constraints from the binding energies of hypernuclei such as 6 ΛΛ He [8], 10 ΛΛ Be [9] and 13 ΛΛ B [10].…”
mentioning
confidence: 99%
“…The HAL QCD potential is obtained from first principles (2+1)-flavor lattice QCD simulations in a large spacetime volume, L 4 = (8.1 fm) 4 , with nearly physical quark masses, (m π , m K )=(146, 525) MeV, at a lattice spacing, a=0.0846 fm. Such simulations together with the HAL QCD method [24,25] enable one to extract the Y N and Y Y interactions with multiple strangeness, e.g.…”
mentioning
confidence: 99%
“…Then, the system is bound more deeply. This gluelike role stabilizes several unstable nuclear systems, like 9 Λ Be [1] and 6 Λ He [2]. Actually, the ground states of 8 Be and 5 He are particle unstable.…”
Section: Introductionmentioning
confidence: 99%